2017
DOI: 10.1016/j.kint.2016.12.020
|View full text |Cite
|
Sign up to set email alerts
|

A composite score associated with spontaneous operational tolerance in kidney transplant recipients

Abstract: New challenges in renal transplantation include using biological information to devise a useful clinical test for discerning high- and low-risk patients for individual therapy and ascertaining the best combination and appropriate dosages of drugs. Based on a 20-gene signature from a microarray meta-analysis performed on 46 operationally tolerant patients and 266 renal transplanted recipients with stable function, we applied the sparse Bolasso methodology to identify a minimal and robust combination of six gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 62 publications
0
40
0
Order By: Relevance
“…Regenerative medicine/tissue engineering can rehabilitate suboptimal donor organs, thereby considerably expanding the current donor organ pool, and has the potential to save the remaining 90%, by generating or repairing organs. Rapid advances are also being made in other areas to increase the donor pool, including xenotransplantation,2 tolerance induction,3 ex vivo perfusion,4 organ preservation and banking,5 and more traditional approaches 6. If the field of transplantation is to be increased tenfold or more in size to fill the expanding need for organ replacement, regenerative medicine will be the major cause of this improvement, but there will be many other secondary causes in addition.…”
Section: Introductionmentioning
confidence: 99%
“…Regenerative medicine/tissue engineering can rehabilitate suboptimal donor organs, thereby considerably expanding the current donor organ pool, and has the potential to save the remaining 90%, by generating or repairing organs. Rapid advances are also being made in other areas to increase the donor pool, including xenotransplantation,2 tolerance induction,3 ex vivo perfusion,4 organ preservation and banking,5 and more traditional approaches 6. If the field of transplantation is to be increased tenfold or more in size to fill the expanding need for organ replacement, regenerative medicine will be the major cause of this improvement, but there will be many other secondary causes in addition.…”
Section: Introductionmentioning
confidence: 99%
“…When applied to stable patients on immunosuppression, the panel identified 7% of patients with a similar, ‘tolerant’ signature, potentially highlighting patients who could be enrolled in trials of drug minimization. Brouard's group has recently reported similar findings for a composite score of a different set of six genes with an equally impressive reported predictive ability . The panel also associated with the development of de‐novo donor‐specific antibody formation.…”
Section: Omics Of Tolerancementioning
confidence: 64%
“…In their study design, they included the same patient groups than in Sagoo et al, but they also included a new group of patients who have undergone clinically driven steroid withdrawal. 135,136 This interesting debate has allowed the definitions of biomarkers of tolerance to be refined. 129 In addition, they also found that azathioprine affected their B cell genetic signature.…”
Section: Other Mechanisms Of Breg Functionmentioning
confidence: 99%
“…129 Their results showed that the percentage of transitional B cells increased significantly after steroid withdrawal, suggesting that the increment of regulatory B cells in tolerant patients could be a consequence of steroid withdrawal rather than a true biomarker of tolerance. 135 Although few studies other than GAMBIT have specifically and the presence of donor-specific antibodies (DSA) were not able to predict late allograft decline. 129 Interestingly, another independent study that evaluated tolerance biomarkers (in particular the expression of IGKV1D-13 and IGKV4-1 genes obtained from Newell et al 125 Having shown that immunosuppressive drugs drastically affect circulating B-cell proportions, it is difficult to conclude with certainty that gene signatures in B cells can be used to indicate operational tolerance in renal transplant recipients.…”
Section: Other Mechanisms Of Breg Functionmentioning
confidence: 99%
See 1 more Smart Citation